Synthesis of 1,2-Diaryl-6,6-dimethyl-5,6-dihydro-1H-indole-4,7-diones from Arylglyoxals and Enamines through Domino Condensation and Allylic Hydroxylation - Maity, Subhendu; Pramanik, Animesh (Synthesis, 2013)
A series of fused pyrrole derivatives, 1,2-diaryl-7-hydroxy-6,6-dimethyl-1,5,6,7-tetrahydro-4H-indol-4-ones, have been synthesized by refluxing mixtures of enamines of 5,5-dimethyl-1,3-cyclohexadione (dimedone) and arylglyoxals in the non-nucleophilic solvent acetonitrile. These pyrrole derivatives are formed through domino condensation of the enamines and arylglyoxals followed by annulation and allylic hydroxylation. Oxidation of the pyrrole derivatives with chromium trioxide in pyridine produced the oxidized products, 1,2-diaryl-6,6-dimethyl-5,6-dihydro-1H-indole-4,7-diones, in good yields.
Keywords: domino reaction; annulation; pyrroles; fused-ring system; heterocycles